Plague and fire: battling black death and the 1900 burning of honolulu´s chinatown - Mohr, James C.
Just as the islands of Hawaii were about to become a U.S. territory, bubonic plague arrived on the shores. In this engrossing story, James Mohr narrates of that anxious visitation and its flaming climax. A huge fire swallowed up Honolulu´s Chinatown. Mohr tells the tale through the perspective of the three more influential players in this drama. Moreover, he tours us through the experience via the eyes of the people caught up in the disaster, from members of the white elite to Chinese doctors, Japanese executives, and Hawaiian reporters. At the core of the narrative are three American physicians -- the Honolulu Board of Health -- who held martial law powers when the government granted them complete control over the armed forces and the treasury. The doctors soon thereafter quarantined Chinatown, where the plague killed on the average one or two people a day and was clearly spreading. The Board of Health members resisted intense pressure from the white community to burn down all of Chinatown. Instead, the Board of Health members ordered a careful, controlled burning of buildings where plague victims had allegedly died. Nevertheless, a freak wind whipped one of those small fires into a roaring inferno that destroyed everything in its path, consuming roughly thirty-eight acres of densely packed wooden structures in a single afternoon. Some 5000 people lost their homes and all their possessions and were marched in shock to detention camps, where they were confined under armed guard for weeks. After the attack on Pearl Harbor in 1941, the Chinatown fire is the worst civic disaster in Hawaiian history.